Influence of Bank Competition and Insurance Penetration on Stock Market Development: Evidence from a Cross-Country Analysis - Budhathok, Prem Bahadur; Ghimire, Shiva Raj; Bhattarai, Ganesh (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study investigated how bank concentration and insurance penetration influence stock market development (SMD) across countries with varying income levels. Design/methodology/approach: This study employed secondary data from 64 nations worldwide from 2000 to 2021. It deployed pooled ordinary least squares, fixedeffect, and random-effect estimators to investigate the impact of bank concentration and insurance penetration on SMD. Findings: The findings revealed that bank concentration negatively impacts SMD, which is significant in the full sample and lower-middle-income economies. However, it is not found to be significant in high-income and upper-middle-income economies. This indicates that the impact of bank concentration on SMD solely depends on the income level of the nation. Conversely, life insurance penetration favorably affects SMD and is robust in all regression models in all economies. By contrast, the findings showed that non-life penetration has a negligible impact on SMD. Conclusion: This study concludes that bank concentration adversely affects SMD in lower-middle-income economies, and insurance penetration favorably impacts SMD in all types of economies. Implications: Since high bank concentration hinders SMD in lower-middle-income nations, policymakers should focus more on increasing bank competition through regulatory reform that encourages new entrants by reducing barriers to entering the market. Policymakers should support life insurance growth by offering tax benefits, raising public awareness, and strengthening regulation to boost investor trust. Originality/value: This study provides novel empirical evidence on the differential impacts of bank concentration and insurance penetration on SMD across highincome, upper-middle-income, and lower-middle-income economies, a critical yet underexplored dimension in financial sector research. JEL Classification: G10, G21, G22